The light and the dark sides of Interleukin-10 in immune-mediated diseases and cancer. (August 2016) - Geginat, Jens; Larghi, Paola; Paroni, Moira; Nizzoli, Giulia; Penatti, Alessandra; Pagani, Massimiliano; Gagliani, Nicola; Meroni, Pierluigi; Abrignani, Sergio; Flavell, Richard A.
Highlights: IL-10 produced by regulatory T-cells has a non-redundant role to maintain intestinal immune homeostasis and to prevent colitis. IL-10 produced by B helper T-cells promotes autoantibody production, and has a pathogenic role in systemic lupus erythematosus. IL-10 produced early by regulatory T-cells or late by helper T-cells might have opposing functions in cytotoxic T-cell responses and cancer. Abstract: Interleukin-10 (IL-10) is known to be a tolerogenic cytokine since it inhibits pro-inflammatory cytokine production and T cell stimulatory capacities of myeloid cells, such as macrophages and dendritic cells. In particular, it has a non-redundant tolerogenic role in intestinal immune homeostasis, since mice and patients with genetic defects in the IL-10/IL-10R pathway develop spontaneously colitis in the presence of a normal intestinal flora. However, IL-10 is also a growth and differentiation factor for B-cells, can promote autoantibody production and has consequently a pathogenic role in systemic lupus erythematosus. Moreover, IL-10 can promote cytotoxic T-cell (CTL) responses and this immunogenic activity might be relevant in type-1 diabetes and anti-tumor immune responses. This review summarizes these paradoxic effects of IL-10 on different types of immune responses, and proposes that different cellular sources of IL-10, in particular IL-10-secreting helper and regulatory T-cells, have different effects on B-cell and CTL responses. Based on this concept we discuss the rationales for targeting the IL-10 pathway in immune-mediated diseases and cancer.